2009
DOI: 10.1111/j.1447-0756.2008.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone mineral density of femur in patients with cervical cancer

Abstract: The results suggest that patients with cervical cancer have low bone mass, especially in the femur, and an increased risk of developing osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
2
6
3
Order By: Relevance
“…Two studies reported that patients with cervical cancer without bone metastases had significantly lower BMD in the LS compared to controls 13 , 14 . On the contrary, Lee et al 25 reported that total femoral BMD, not spinal BMD, was significantly lower in patients with cervical cancer compared to controls, and it is contrary to other studies including ours.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Two studies reported that patients with cervical cancer without bone metastases had significantly lower BMD in the LS compared to controls 13 , 14 . On the contrary, Lee et al 25 reported that total femoral BMD, not spinal BMD, was significantly lower in patients with cervical cancer compared to controls, and it is contrary to other studies including ours.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, there were no significant differences of basal BMD in the LS and femur between patients with endometrial cancer and controls, and it is similar to the result of Lee et al 15 . We hypothesized that BMD values at the LS and femur were not different between two groups because bone mass in patients with endometrial cancer may have reached a balance between the negative effect of CIBL and the positive effect of high endogenous estrogen levels related to endometrial cancer 28 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lee and colleagues [15] retrospectively analyzed the BMD of the spine and femur using DXA in 31 patients with endometrial cancer without bone metastases and 61 controls who were treated with surgery for benign disease in Korea. These authors reported no differences in the BMD of the spine or femur between patients with endometrial cancer and controls.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of neoplasms without bone metastasis are also known to be related to osteoporosis by producing circulating bone resorption stimulatory factors, leading to bone destruction and hypercalcemia [7][8][9][10][11][12]. In patients with gynecologic cancers, reduced spinal BMD has been reported in patients with cervical cancer [13,14], but no significant differences were found in spinal or femoral BMD between patients with endometrial cancer and controls [15].…”
Section: Ivyspringmentioning
confidence: 99%